Swimming in warm water is ineffective in heat acclimation and is non-ergogenic for swimmers - Bradford, C. D.; Lucas, S. J. E.; Gerrard, D. F.; Cotter, J. D. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Heat acclimation (HA) in air confers adaptations that improve exercise capabilities in hot and possibly temperate air. Swimmers may benefit from HA, yet immersion may constrain adaptation. Therefore, we examined whether warm-water swimming constitutes effective HA. In a randomized-crossover study, eight male swimmers swam 60?min/day on 7 days in 33 °C (HA) or 28 °C (CON) water. They performed 20-min distance trials before and after each regime: in 33 °C water (Warm); 28 °C water (Temperate); and cycling in 29 °C air (Terrestrial) following standardized exercise. Rectal temperature (Tre) rose ~ 1 °C in HA sessions, and sweat loss averaged 1.4 L/h. After accounting for CON, HA did not confer any clear expansion of plasma volume [1.9% (95% CI: 7.7)], reduction in heart rate during standardized cycling exercise [1 b/min (9)], reduction in Tre during rest [+0.1 °C (0.1)] or exercise, or change in sudomotor function. Only perceived temperature and discomfort tended to improve. Performance was clearly not improved for Warm [+0.3% (1.8)] or Temperate [+0.3% (1.9)], was unclear for Terrestrial [+0.4% (17.7)], and was unrelated to changes in resting plasma volume (r < 0.3). In conclusion, short-term HA using swimming in 33 °C water confers little adaptation and is not ergogenic for warm or temperate conditions.